Desenvolvimento de uma Infraestrutura baseada em HL7® FHIR® para Interoperabilidade Clínica - Gonçalves, Tiago Tavares (2021)
Throughout the years, the healthcare business knowledge, requirements, and the number of patients seeking medical attention has grown tremendously to a point where sensitive cases needed the input from multiple healthcare institutions in order to track the patient’s medical history and make the most adequate decisions for each situation. Technology and digital information fulfils a great role in addressing these problems and improving healthcare provision. However, due to the immense number of organizations and systems in this business, sharing a patient’s clinical information can be a major problem if the systems are not capable of understanding the data sent to each other. Ensuring interoperability between systems is crucial to guarantee the continuous flow of a patient’s clinical history transmission and to improve the health professionals’ work. As a company working in the field of healthcare, ALERT’s main goal is to help organizations improve in their health business and to help prolong life, by providing the necessary technology that is capable of benefiting the health professional’s work management and sharing the necessary information with other organizations. Thus, the company seeks to constantly improve its product suite, ALERT®, by meeting the worldwide organizations requirements and assuring interoperability based on the existing health standards in the market. This way, the company wants to add in the ALERT suite the latest standard, Fast Healthcare Interoperability Resources (FHIR ® ), which brings great technological innovations for interoperability’s improvement, provided by the standards developing organization, Health Level Seven International (HL7), being also considered to be a suitable standard for mobile applications thanks to its capabilities and ease of implementation. Herewith, thisthesis presents a development and architectural approach to apply FHIR features in the product suite, along with the problem and solution analysis, including the evaluation of suitable frameworks for the implementation phase. Considering the experiments’ results, the implemented FHIR services actually improved the product’s performance, and thanks to the standard’s specification, the implementation of its core features proved to be simple and straightforward while respecting the key criteria for some of the developed services.